Comparative study of porphyrin derivatives in monolayers at the air-water interface and in langmuir-blodgett films - Ghosh, Amrita; Mahato, Prasenjit; Choudhury, Sipra; Das, Amitava (Thin Solid Films, 2011)
The orientation and aggregation of various porphyrin derivatives at the air–water interface and in Langmuir–Blodgett films were investigated. Monolayer properties of these molecules, where long alkyl chain(s) were covalently bound through different functionality of varying hydrophilicity were studied by measuring surface pressure area isotherms. Such derivatives, where ether functionality (functionalities) was (were) used for linking long alkyl chain(s), did not form uniform monolayer; instead they were found to form multilayer clusters or aggregates on the water surface. On the other hand, porphyrin derivative functionalized at the four peripheral phenyl rings with eight hexadecyl ether chains formed stable spherical vesicles when deposited on mica. Tetra N-alkyl pyridinium porphyrins with long alkyl chain were found to form various phases on the water surface. Evidence of transition from horizontal orientation to vertical orientation of porphyrin rings of porphyrin molecules having C14 chains was observed. This type of transition was lost with the porphyrin molecule with a relatively smaller chain (C8).

Competitive binding of Ba2+and Sr2+ to 18-crown-6 in a receptor with a 1-methoxyanthraquinone analogue as the other binding site - Banerjee, Tanmay; Suresh, Moorthy; Ghosh, Hirendra N.; Das, Amitava (Europian Journal of Inorganic Chemistry, 2011)
Owing to their immense biological significance, development of sensors for the selective detection of alkaline earth metal ions has attracted vast research interest. In this article we have reported the synthesis, characterisation and ion binding studies of a new RuII-polypyridyl-crown-anthraquinone complex (5). Studies confirm selective binding of BaII, SrII and CaII ions, with Kmath image > Kmath image >> Kmath image, over all other metal ions, to the crown ether moiety and not to the methoxy anthraquinone component, the latter being the second binding site available and known for its affinity towards alkaline earth metal ions from one of our previous reports.

CN? specific turn-on phosphorescent probe with probable application for enzymatic assay and as an imaging reagent - Reddy, Upendar G.; Das, Priyadip; Saha, Sukdeb; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Chemical Communications, 2013)
A new “turn-on” luminescence probe for imaging the uptake of 0.2 ppm inorganic CN− in live HeLa cells as well as for probing the CN− generation through an enzymatic process in a virtual aqueous medium at appropriate pH.

Can silicon substituted metal-free organic dyes achieve better efficiency compared to silicon free organic dyes? a computational study - Biswas, Abul Kalam; Das, Amitava; Ganguly, Bishwajit (Physical Chemistry Chemical Physics, 2015)
The power conversion efficiency of metal-free organic dyes in dye-sensitized solar cells (DSSCs) is now comparable to ruthenium-based polypyridyl and zinc-based porphyrin dyes. We have computationally investigated the structural, electronic and optical properties of a series of metal free organic dyes and their corresponding silicon substituted dyes. The DFT and TD-DFT calculations revealed that silicon substituted organic dyes have higher efficiency than the corresponding silicon free organic dyes. The computational results showed that the presence of silole units as a spacer group can significantly affect the performance of DSSCs compared to typically using thiophene as a spacer unit. These results corroborate the experimental observations reported in the literature. The time-dependent density functional theory (TDDFT) calculations performed at the CPCM-CAM-B3LYP/6-31+G* level of theory showed better agreement with the experimental absorption spectra of some reported metal free organic dyes having silole in the spacer group compared to other functionals and are employed in this study. Indoline donor based dye 5 showed a much shorter absorption spectrum (absorption peak at 425 nm) and smaller electron injection driving force (Delta G(injection) = -1.77 eV) than the corresponding dye 8 containing silicon substituted indoline as a donor and a silole group as a spacer unit. lambda(max) = 502 nm and Delta G(injection) = -1.82 eV calculated for dye 8 are much larger than the corresponding silicon free dye 5. The silicon based dye 8 helps in achieving a much lower DGregeneration value than 5, which can facilitate the faster electron injection rate from the dye to the semiconductor TiO2. Dye 8 should also have a higher V-oc value compared to other dyes (5-7) due to favourable interaction with the electrolyte (I-/I-3(-)). The higher planarity and better conjugation in dye 8 facilitate the transfer of electrons from the dye molecules to the semiconductor TiO2. The calculations performed with phenyl protecting groups near the silicon center of the dye molecule 8 to diminish the dimerization process showed very similar optical properties as obtained with the corresponding unprotected dye system. The designed julolidine and pyrrolo-indolizine donor based dyes also showed a similar trend as observed for indoline donor based dyes.

Cytostatic ruthenium(II)-platinum(II) bis(terpyridyl) anticancer complex that blocks entry into sphase by up-regulating p27(KIP1) - Ramu, Vadde; Gill, Martin R.; Jarman, Paul J.; Turton, David; Thomas, Jim A.; Das, Amitava; Smythe, Carl (Chemistry-A European Journal, 2015)
Cytostatic agents that interfere with specific cellular components to prevent cancer cell growth offer an attractive alternative, or complement, to traditional cytotoxic chemotherapy. Here, we describe the synthesis and characterization of a new binuclear Ru-II-Pt-II complex [Ru(tpy)(tpypma)Pt(Cl)(DMSO)](3+) (tpy=2,2:6,2-terpyridine and tpypma=4-([2,2:6,2-terpyridine]-4-yl)-N-(pyridin-2-ylmethyl)aniline), VR54, which employs the extended terpyridine tpypma ligand to link the two metal centres. In cell-free conditions, VR54 binds DNA by non-intercalative reversible mechanisms (K-b=1.3x10(5)M(-1)) and does not irreversibly bind guanosine. Cellular studies reveal that VR54 suppresses proliferation of A2780 ovarian cancer cells with no cross-resistance in the A2780CIS cisplatin-resistant cell line. Through the preparation of mononuclear Ru-II and Pt-II structural derivatives it was determined that both metal centres are required for this anti-proliferative activity. In stark contrast to cisplatin, VR54 neither activates the DNA-damage response network nor induces significant levels of cell death. Instead, VR54 is cytostatic and inhibits cell proliferation by up-regulating the cyclin-dependent kinase inhibitor p27(KIP1) and inhibiting retinoblastoma protein phosphorylation, which blocks entry into Sphase and results in G1 cell cycle arrest. Thus, VR54 inhibits cancer cell growth by a gain of function at the G1 restriction point. This is the first metal-coordination compound to demonstrate such activity.
Keywords: antitumor agents; cytostatic; p27KIP1; platinum drugs; ruthenium terpyridine

Charge delocalization in the cascade band structure CdS/CdSe and CdS/CdTe core-shell sensitized with Re(I)-polypyridyl complex - Maity, Partha; Debnath, Tushar; Banerjee, Tanmay; Das, Amitava; Ghosh, Hirendra N. (Journal of Physical Chemistry C, 2016)
Charge-carrier dynamics of CdS quantum dot (QD) and CdS/CdSe type-I and CdS/CdTe type-II core shell nanocrystals (NCs) sensitized with a Re(I)-polypyridyl complex have been carried with special emphasis on studies on carrier delocalization and the role of Re-complex as a hole acceptor and sensitizer molecule. Our investigation confirmed photoexcited hole transfer from CdS and CdS/CdSe to the Re-complex, while no hole transfer was observed in the CdS/CdTe Re-complex system. This was rationalized by the evaluation of the relative energy levels, which revealed that such hole migration was not energetically favorable due to low-lying highest occupied molecular orbital (HOMO) of the Re-complex as compared with the valence band (VB) of CdTe shell; however, luminescence quenching from upper excited states of Re-complex was observed in the presence of all three QD and core shell systems, which has been attributed to electron injection from hot state (energetically higher than the LUMO state) of the Re-complex to the conduction band (CB) of the QDs. Transient absorption (lambda(pump) = 400 nm, lambda(probe) = 450-750 nm) spectra recorded for Re complex-sensitized CdS and CdS/CdSe composite in the femtosecond time domain revealed a broad transient absorption band in the 580-750 nm region with a peak around 595 nm, and this was attributed to the cation radical formation for Re-complex, either by capturing photoexcited hole from the NCs or by injecting electron to the CB of the NCs. As anticipated, no such spectrum was observed for the CdS/CdTe Re-complex composite system after 400 nm excitation. Electron injection from photoexcited Re-complex to CdS QD and CdS/CdSe core shell was found to be <100 fs, while the hole transfer from photoexcited CdS QD and CdS/CdSe core shell to Re-complex took place within the time scale of 900 fs and 2.5 ps, respectively.

Counteranion driven homochiral assembly of a cationic C-3-symmetric gelator through ion-pair assisted hydrogen bond - Maity, Arunava; Gangopadhyay, Monalisa; Basu, Arghya; Aute, Sunil; Babu, Sukumaran Santhosh; Das, Amitava (Journal of the American Chemical Society, 2016)
The helical handedness in achiral self-assemblies is mostly complex due to spontaneous symmetry breaking or kinetically controlled random assembly formation. Here an attempt has been made to address this issue through chiral anion exchange. A new class of cationic achiral C-3-symmetric gelator devoid of any conventional gelation assisting functional units is found to form both right-and left-handed helical structures. A chiral counteranion exchange-assisted approach is successfully introduced to control the chirality sign and thereby to obtain preferred homochiral assemblies. Formation of anion-assisted chiral assembly was confirmed by circular dichroism (CD) spectroscopy, microscopic images, and crystal structure. The X-ray crystal structure reveals the construction of helical assemblies with opposite handedness for (+)- and (-)-chiral anion reformed gelators. The appropriate counteranion driven ion-pair-assisted hydrogen-bonding interactions are found responsible for the helical bias control in this C-3-symmetric gelator.

Cysteine-specific fluorescent switch for monitoring oxidative stress and quantification of aminoacylase-1 in blood serum - Anila, H. A.; Ali, Firoj; Kushwaha, Shilpi; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Analytical Chemistry, 2016)

Chiral discrimination through h-1 nmr and luminescence spectroscopy: dynamic processes and solid strip for chiral recognition - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Rajamohanan, P. R.; Ravindranathan, Sapna; Das, Amitava (Chemistry-A European Journal, 2017)
The appropriate choice of the host molecules with well-defined optical activity (S-H/R-H) helps in the differentiation between two secondary ammonium ion-derivative guest molecules with different optical activities (R-G/S-G) based on the fluorescence resonance energy transfer (FRET)based luminescence responses. Crown ether-based host molecules with opposite chiral configurations (R-H, S-H) have been derived from 1,1'-bi-2-naphthol (BINOL) derivatives that have axially chiral biaryl centers. These chiral crown ethers form host-guest complexes (i.e., [2] pseudoro-taxanes) with chiral secondary ammonium ion derivatives (R-G, S-G). NMR spectroscopic studies show that the complexes are in a dynamic equilibrium in solution. Results of the H-1 NMR and fluorescence spectroscopic studies indicate a head-on orientation of the host and guest in the [2] pseudorotaxanes. The difference in the efficiency in the FRET-based responses between anthracene and the BINOL derivatives allow efficient chiral discrimination of the guests. Isothermal titration calorimetry and NMR investigations reveal that inclusion complexes between hosts and guests of the same chirality (R-H center dot R-G, S-H center dot S-G) are more stable relative to those of opposite chirality (R-H center dot S-G, S-H center dot R-G). However, FRET-based energy-transfer efficiency is higher for R-H center dot S-G and S-H center dot R-G complexes. NMR spectroscopic studies show that the relative orientation of the guest in the host cavity is significantly different when the host binds a guest of the same or opposite chirality; furthermore, the latter is more favorable for FRET, thus enabling discrimination between enantiomers. Interestingly, chiral discrimination of guest ions could also be achieved by using silica surfaces modified with chiral host molecules.

Cucurbit[7]uril induced formation of fret-enabled unilamellar lipid vesicles - Kushwaha, Shilpi; Maity, Arunava; Gangopadhyay, Monalisa; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Das, Amitava (Langmuir, 2017)
A unique fluorescence resonance energy transfer (FRET) process is found to be operational in a unilamellar lipid self-assembly in the aqueous phase. A newly synthesized naphthyl based long chain lipid derivative [N-(naphthalene-1-ylmethyl)tetradecane-1-ammonium chloride, 14NA(+)] forms various self-assembled architectures in the aqueous phase. Controlled changes in lipid concentration lead to a transition of the self-assemblies from micelles to vesicles to rods. In the presence of cucurbit[7]uril (CB7), 14NA(+) forms a host-guest [2]pseudorotaxane complex (CB7(sic)14NA(+)) and secondary interactions lead to the formation of a lipid bilayer with hydrophobic pockets situated in between the layers. The change in the structure of 14NA(+) assemblies, interaction with CB7 and formation of supramolecular assemblies of CB7(sic)14NA(+) were examined using light scattering, spectroscopic, and microscopic techniques. Entrapment of a luminescent dye, anthracene within the hydrophobic bilayer of the supramolecular assembly CB7(sic)14NA(+) favors a modified luminescent response due to an efficient FRET process. Further, the FRET process could be controlled by thermal and chemical stimuli that induce transformation of unilamellar vesicles.